Differentiated fit and shared values: Alternatives for managing headquarters‐subsidiary relations - Nohria, Nitin; Ghoshal, Sumantra (Strategic Management Journal, 1994)
Abstract This paper elaborates and provides empirical support for two different approaches to managing the nexus of headquarters subsidiary relations in a multinational corporation (MNC). The first approach is that of Differentiated Fit. We show that the extent to which an MNC differentiates the formal structure of its headquarters subsidiary relations to fit the contexts of its various subsidiaries, the better the performance of the MNC as a whole. The second approach is that of Shared Values. We show that a high degree of shared values among the headquarters and subsidiaries is another approach to governing headquarterssubsidiary relation that enhances the performance of the MNC. We further maintain that differentiated fit and shared values, while being alternatives, are not mutually exclusive ways of effectively managing headquarters subsidiary relations. Indeed, MNCs that can simultaneously implement these two approaches have the best relative performance.